Profiling and assessing the risks of image- and performance-enhancing drugs use during the COVID-19 lockdown - Ilaria De Luca; Francesco Di Carlo; Julius Burkauskas; Artemisa R. Dores; Artemisa R. Dores; Irene P. Carvalho; M. Ángeles Gómez-Martínez; Attila Szabo; Attila Szabo; Hironobu Fujiwara; Hironobu Fujiwara; Hironobu Fujiwara; et al. (Frontiers Media S.A., 2024)
BackgroundImage and Performance-Enhancing Drugs (IPEDs) can enhance mental and physical capabilities and impact one's overall health. Initially confined in sport environments, IPEDs use has become increasingly widespread in a high-performing society. The present study was aimed at profiling IPEDs use during the COVID-19 lockdown among an international sample of young adults.MethodsA cross-sectional observational study was carried out in eight countries (United Kingdom, Italy, Lithuania, Hungary, Portugal, Spain, Brazil, and Japan) between April and May 2020. The survey questionnaire included validated measurements such as Exercise Addiction Inventory (EAI), Appearance Anxiety Inventory (AAI), and Self-Compassion Scale (SCS) as well as questions about the type of IPEDs, purchasing methods and socio-demographic information.ResultsA total of 736 IPEDs users were included in the survey. Their mean age was 33.05 years (±SD = 10.06), and 64.2% were female participants. Overall, 6.8% were found at risk of exercise addiction (EAI >24), 27.6% presented high levels of appearance anxiety, and 24.9% revealed low levels of emotional regulation's self-compassion. Most participants (55.6%) purchased IPEDs through pharmacies/specialized shops, while 41.3% purchased IPEDs on the Internet. Online IPEDs buyers were mainly men who had higher scores on the Exercise Addiction Inventory. One or more IPEDs classifiable as "potentially risky" were used by 66.3% of the sample. Users of "potentially risky IPEDs" were younger and primarily men. They showed higher scores both on the Exercise Addiction Inventory and Appearance Anxiety Inventory.ConclusionThis study profiled users of IPEDs when the most restrictive COVID-19 lockdown policies were implemented in all the participating countries. More targeted post-COVID 19 prevention strategies should be implemented according to the emerged socio-demographic and psychopathological traits and cross-cultural differences emerged. Longitudinal studies will also be needed to determine the long-term effect of the COVID-19 lockdown on IPEDs consumption.